the FORMULATION AND EVALUATION OF HERBAL BATH SOAP CONTAINING METHANOLIC EXTRACTS OF THREE AYURVEDIC VARNYA HERBS - GANA MANJUSHA K; BALAKRISHNAIAH P; SYAMALA R; MOUNIK N; RAVI CHANDRA T (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The ultimate aim of this study is to formulate and evaluate the herbal bath soap using methanolic extracts of three plants having ethnic and dermatological importance in Ayurveda, namely, Hemidesmus indicus, Cyperus rotundus, and Saussurea lappa. Methods: The roots of H. indicus and S. lappa and rhizomes of C. rotundus were extracted with ethanol using Soxhlet apparatus. Then, these extracts were used to make soap by reacting oil and lye in a process of saponification. Results: The soap made was evaluated for physicochemical characters such as total fatty matter, moisture content, and pH and found to be 77, 5.3%, and 8 and for other parameters, good characteristics were observed. Discussion: The soap also exhibited good cleaning efficiency in removing microbes on hands. Conclusion: Hence, based on the antimicrobial effects and parameters, the formulated soap can further be standardized and an alternative to commercial medicinal and skin whitening soaps.